Assessing the safety, impact and effectiveness of RTS,S/AS01E malaria vaccine following its introduction in three sub-Saharan African countries: methodological approaches and study set-up - Nicolas Praet; Kwaku Poku Asante; Marie‐Cécile Bozonnat; Elaine Jacqueline Akité; Patrick Ansah; Laurence Baril; Owusu Boahen; Yolanda Guerra Mendoza; Valérie Haine; Simon Kariuki; Mathieu Lamy; Kenneth Maleta; et al. (2022)
Abstract Background Following a 30-year development process, RTS,S/AS01 E (GSK, Belgium) is the first malaria vaccine to reach Phase IV assessments. The World Health Organization-commissioned Malaria Vaccine Implementation Programme (MVIP) is coordinating the delivery of RTS,S/AS01 E through routine national immunization programmes in areas of 3 countries in sub-Saharan Africa. The first doses were given in the participating MVIP areas in Malawi on 23 April, Ghana on 30 April, and Kenya on 13 September 2019. The countries participating in the MVIP have little or no baseline incidence data on rare diseases, some of which may be associated with immunization, a deficit that could compromise the interpretation of possible adverse events reported following the introduction of a new vaccine in the paediatric population. Further, effects of vaccination on malaria transmission, existing malaria control strategies, and possible vaccine-mediated selective pressure on Plasmodium falciparum variants, could also impact long-term malaria control. To address this data gap and as part of its post-approval commitments, GSK has developed a post-approval plan comprising of 4 complementary Phase IV studies that will evaluate safety, effectiveness and impact of RTS,S/AS01 E through active participant follow-up in the context of its real-life implementation. Methods EPI-MAL-002 (NCT02374450) is a pre-implementation safety surveillance study that is establishing the background incidence rates of protocol-defined adverse events of special interest. EPI-MAL-003 (NCT03855995) is an identically designed post-implementation safety and vaccine impact study. EPI-MAL-005 (NCT02251704) is a cross-sectional pre- and post-implementation study to measure malaria transmission intensity and monitor the use of other malaria control interventions in the study areas, and EPI-MAL-010 (EUPAS42948) will evaluate the P. falciparum genetic diversity in the periods before and after vaccine implementation. Conclusion GSK’s post-approval plan has been designed to address important knowledge gaps in RTS,S/AS01 E vaccine safety, effectiveness and impact. The studies are currently being conducted in the MVIP areas. Their implementation has provided opportunities and posed challenges linked to conducting large studies in regions where healthcare infrastructure is limited. The results from these studies will support ongoing evaluation of RTS,S/AS01 E ’s benefit-risk and inform decision-making for its potential wider implementation across sub-Saharan Africa. Graphic abstract